PEMANFAATAN KEGIATAN SERIASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS ANAK USIA 4-5 TAHUN DI PAUD MUTIARA HATI KECAMATAN KARANG INTAN - Muflihah; Baiti , Noor; Nisa, Uswatun; Zulkarnaen, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve the logical thinking skills of children aged 4–5 years through the use of seriation activities at PAUD Mutiara Hati, Karang Intan District. This research employed a qualitative approach with a Classroom Action Research design based on the Kemmis and McTaggart model, conducted in two cycles with two meetings in each cycle. The subjects of the study were 10 children in Group A, consisting of 4 boys and 6 girls. Data were collected through observation and documentation. The results showed an improvement in children’s logical thinking skills at each meeting. In the pre-cycle stage, most children were in the Not Yet Developed (BB) category at 80% and the Beginning to Develop (MB) category at 20%. In Cycle I Meeting 1, 50% of the children were in the MB category and 50% in the Expected Development (BSH) category. In Cycle I Meeting 2, 40% were in the MB category and 60% in the BSH category. In Cycle II Meeting 1, 10% were in the MB category, 50% in the BSH category, and 40% in the Very Well Developed (BSB) category. Finally, in Cycle II Meeting 2, 20% of the children were in the BSH category and 80% were in the BSB category. These findings indicate that seriation activities were effective in improving the logical thinking skills of children aged 4–5 years.